Teamwork and Students’ Perceptions of Fairness and Self-Regard: a Mixed-Method Exploration - Hanh Nguyen; Ngan Le; Tien Phan (Universitas Ahmad Dahlan, 2026)
This research examines how structured teamwork in an English as a Foreign Language (EFL) course relates to Vietnamese university students’ perceptions of fairness and self-regard. Grounded in social interdependence theory and organizational justice theory, the study employed a mixed-method approach over eight weeks with 143 freshmen enrolled in a beginning-level English communication course. Quantitative data were collected through pre- and post-course surveys, teamwork rubric ratings, and group presentation scores, while qualitative data were gathered through team reports and semi-structured interviews. Results showed substantial pre–post increases in fairness and self-regard. However, teamwork performance indicators were not directly associated with changes in either construct. In contrast, teamwork quality was positively related to presentation performance, and qualitative evidence suggested that equitable task division, open communication, and respectful collaboration were linked to students’ perceptions of fairness and confidence. Overall, the findings suggest that teamwork may support fairness and self-regard through collaborative processes rather than through measurable teamwork scores alone. This study highlights the social–emotional value of teamwork-based instruction and underscores the importance of clear role assignment, shared responsibility, and communication routines in EFL classrooms.